Stable Cryptocurrencies - Craig Calcaterra; Wulf A Kaal; Vadhindran Rao (Washington University Journal of Law & Policy, 2020)
The authors examine the emergence and proliferation of stable cryptocurrencies and their uses. After evaluating the core shortcomings associated with fiat currencies, the authors highlight the benefits of stable cryptocurrencies for monetary policy making, overall market stability, and their bilateral impact on the emergence of decentralized commerce. The transition to digital currencies has already started. It is a matter of time until the use cases and applications of stable cryptocurrencies become more mainstream.
Keywords: cryptocurrency; monetary policy